2021
DOI: 10.1007/s12220-021-00701-5
|View full text |Cite
|
Sign up to set email alerts
|

A Differential Perspective on Gradient Flows on $$\textsf {CAT} (\kappa )$$-Spaces and Applications

Abstract: We review the theory of Gradient Flows in the framework of convex and lower semicontinuous functionals on $$\textsf {CAT} (\kappa )$$ CAT ( κ ) -spaces and prove that they can be characterized by the same differential inclusion $$y_t'\in -\partial ^-\textsf {E} (y_t)$$ y t ′ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…HS m is obtained under the same assumptions. We report below the detailed computation showing that the stronger bound (2.7) actually holds and fixing a typo in [40].…”
Section: Energy and Non-linear Harmonic Mapsmentioning
confidence: 93%
See 1 more Smart Citation
“…HS m is obtained under the same assumptions. We report below the detailed computation showing that the stronger bound (2.7) actually holds and fixing a typo in [40].…”
Section: Energy and Non-linear Harmonic Mapsmentioning
confidence: 93%
“…HS , see for instance [60,Chapter 8]. This is generalized to the present setting in [40,Theorem 4.1]. See also [74] for the case of maps with Euclidean source and CAT(0) target.…”
Section: Energy and Non-linear Harmonic Mapsmentioning
confidence: 97%
“…while, on the other hand, Z 1 ∩ E ε (z) has a density point in z. Then, according to (12), we can deduce that…”
Section: Convergence Of the Korevaar-schoen Potentialsmentioning
confidence: 90%
“…This functional was first introduced in [20], as the key tool to study the harmonicity of maps defined from a smooth manifold to a general metric space (see also [19]). We point out that recently this energy has been a central object of investigation in a series of works [13,12,14], where it was extended to maps defined on more general RCD spaces. Notice that since this new distance d ′ is defined intrinsically, it will be in particular canonical, meaning that it will depend only on the space and not on particular choices of some other geometric objects.…”
Section: Introductionmentioning
confidence: 99%
“…Notice in particular that the key 'subpartition lemma' from [60] may fail in this framework. This motivated us to develop a research program [46,45,24,40,37], in collaboration with a diverse set of coauthors, aimed at generalizing the above to its natural framework of RCD spaces. In particular, in [46], suitably adapting Korevaar-Schoen's approach, we showed that the Dirichlet problem is well posed in this framework, so that at least the concept of 'harmonic map from a domain in an RCD(K, N ) space to a CAT(0) one' is well defined.…”
Section: Introductionmentioning
confidence: 99%